Influence of Inventory Management on Performance of the Private Commercial banks in Kenya - Kithae, Samuel; Achuora, John (My University, 2017)
Purpose: The goal of the study was to examine the influence of inventory management on performance of private commercial banks in Kenya, with an aim of making recommendations on proper use of inventory management practices. Methodology: This research study adopted a descriptive research design approach. The researcher preferred this method because it allowed an in-depth study of the subject. The target population was all the 220 procurement officers in the private commercial banks in Kenya. From the three strata, a sample of 142 respondents was selected using simple random sampling. Data was collected using self-administered questionnaires. The data collected was analyzed by use of descriptive and inferential statistics. Multiple regression model was used to show the relationship between the dependent variable and the independent variables. Results: In regard to information technology, the regression coefficients of the study show that it has a significant influence of 0.752 on performance of private commercial banks. Second in regard to warehouse management system, the regression coefficients of the study show that it has a significant influence of 0.156 on performance of private commercial banks.With regard to the third objective, the regression coefficients of the study show inventory cycle counting has a significant influence of 0.06 on performance of private commercial banks. Lastly, in regard to the fourth objective, the regression coefficients of the study show warehousing management system has a significant influence of 0.02 on performance of private commercial banks. Conclusion: The findings of the study concluded that information technology, inventory control techniques, inventory cycle counting and warehousing management system have a positive relationship with performance in private commercial banks. Policy recommendation: the study recommended that private institutions should embrace inventory management practices so as to improve their performance and further researches should to be carried out in other private institutions to find out if the same results can be obtained.
Keywords: Inventory control techniques; Information technology; Warehouse management system; Inventory cycle counting